The tracking and erosion performance of silicone rubber incorporated with novel TiO2@SiO2 core-shell nano fillers under the IEC 60587 standard - Usama Asad; Salman Amin; Muhammad Haris Aziz; Muhammad Awais; Taqi ur Rahman; Hassan Ahmed Awan (Materials Research Express, 2020)
In last two decades a promising performance improvement in the electrical insulation materials has been reported by many researchers using different nano fillers (NFs). In recent years another type of NFs called core–shell type nano fillers have shown even more attention than ordinary NFs. The core–shell NFs are a combination of nano particle core coated with outer nano layer of different material. The core–shell NFs combine the beneficial properties of two material with in one NF. Recently a few studies have reported a considerable improvement in the dielectric properties of epoxy by utilising TiO _2 @SiO _2 core–shell NFs. The TiO _2 @SiO _2 particles have a core of TiO _2 coated with an out layer of SiO _2 at nano level. This study investigates the improvement in tracking performance of silicone rubber (SiR) using TiO _2 @SiO _2 core–shell nano particles which has not been reported previously. The tracking immunity of low (below 1%) and high (above 1%) filler concentrations of nano TiO _2 @SiO _2 incorporated into SiR was investigated according to IEC 60587. The results showed that an optimum percentage of 0.6 wt% of TiO _2 @SiO _2 imparts best immunity to silicone rubber against tracking.